Association of Intraventricular Fibrinolysis With Clinical Outcomes in Intracerebral Hemorrhage: An Individual Participant Data Meta-Analysis. Issue 9 (6th May 2022) - Kuramatsu, Joji B.; Gerner, Stefan T.; Ziai, Wendy; Bardutzky, Jürgen; Sembill, Jochen A.; Sprügel, Maximilian I.; Mrochen, Anne; Kölbl, Kathrin; Ram, Malathi; Avadhani, Radhika; Falcone, Guido J.; Selim, Magdy H.; et al.
Abstract : Background: In patients with intracerebral hemorrhage (ICH), the presence of intraventricular hemorrhage constitutes a promising therapeutic target. Intraventricular fibrinolysis (IVF) reduces mortality, yet impact on functional disability remains unclear. Thus, we aimed to determine the influence of IVF on functional outcomes. Methods: This individual participant data meta-analysis pooled 1501 patients from 2 randomized trials and 7 observational studies enrolled during 2004 to 2015. We compared IVF versus standard of care (including placebo) in patients treated with external ventricular drainage due to acute hydrocephalus caused by ICH with intraventricular hemorrhage. The primary outcome was functional disability evaluated by the modified Rankin Scale (mRS; range: 0–6, lower scores indicating less disability) at 6 months, dichotomized into mRS score: 0 to 3 versus mRS: 4 to 6. Secondary outcomes included ordinal-shift analysis, all-cause mortality, and intracranial adverse events. Confounding and bias were adjusted by random effects and doubly robust models to calculate odds ratios and absolute treatment effects (ATE). Results: Comparing treatment of 596 with IVF to 905 with standard of care resulted in an ATE to achieve the primary outcome of 9.3% (95% CI, 4.4–14.1). IVF treatment showed a significant shift towards improved outcome across the entire range of mRS estimates, common odds ratio, 1.75 (95% CI, 1.39–2.17), reduced mortality, odds ratio, 0.47 (95% CI, 0.35–0.64), without increased adverse events, absolute difference, 1.0% (95% CI, −2.7 to 4.8). Exploratory analyses provided that early IVF treatment (≤48 hours) after symptom onset was associated with an ATE, 15.2% (95% CI, 8.6–21.8) to achieve the primary outcome. Conclusions: As compared to standard of care, the administration of IVF in patients with acute hydrocephalus caused by intracerebral and intraventricular hemorrhage was significantly associated with improved functional outcome at 6 months. The treatment effect was linked to an early time window <48 hours, specifying a target population for future trials.